A Labor View on the Social Clause - Bagtas, Cedric R. (Kasarinlan: Philippine Journal of Third World Studies, 2011)
The article argues for the need for a social clause in the last General Agreement on Tarrifs and Trade (GATT) treaty. Experts assert that social clauses and related sanctions cannot effectively compel the enforcement of labor laws. Also, there exists a contention that workers’ rights could become the basis for putting up unjust barriers to world trade. In spite of these, the paper insists that a social clause is necessary to ensure the protection of fundamental laborers’ rights in GATT member-countries. It condemns the governments and employers that seek the elimination of the social clause, decrying their complicity in the exploitation of laborers and the rejection of trade union rights in order to gain an unfair advantage over countries that are more conscientious about the needs of their workers. It chastises the Philippine government for implicitly siding with these governments, despite its averred advocacy of workers’ rights. It seeks an appreciation of the assertion that providing laborers with a means to combat abuses against their basic rights is in line with the development of a level playing field in international trade. While a social clause may not be a priority at present, there is hope that there will be deliberations about it in future trade agreements.
Keywords: GATT · workers’ rights · international trade · Philippines